Trauma in children - Kazez, Ahmet (Galenos Yayincilik, 2010)
Children are still and exposed to trauma at high rates. Traumatic injuries are the second leading cause of emergency department visits after infections. Almost half of child mortality are caused by the traumatic injuries. The aim of this study was to present childhood traumas, focusing on the aspects important with respect to pediatric practice. (Turk Arch Ped 2010; 45 Suppl: 12-6)
Çocuklarda travma
Keywords: Abuse; child; trauma; newborn